Preparation of Organic Amine-Intercalated Magnesium Phosphate and Magnesium Boron Phosphate and Their Tribological Properties as a Solid Lubricant - MA Chong, XU Xiaoqi, KONG Xiaowei, LI Yanqiu, ZHANG Yanfei, QIAO Li, HE Xuexue, LI Kangwei, ZHANG Xiaosheng, LIU Lei (Cailiao Baohu)
With the development of modern industry，the demand for lubrication in various working environments has become increasingly stringent.Conventional lubricants can no longer fully meet the performance requirements of mechanical operating conditions，making the development of new lubricants a critical research focus.To meet the requirements of comprehensive salt-lake resource utilization，two novel solid lubricant materials，organic amine-intercalated magnesium phosphate (MgP-18N) and organic amine-intercalated magnesium boron phosphate (BP-18N)，were prepared via a mixed solvothermal method.Their tribological properties as lithium-based grease additives were investigated using an oscillating ball-on-disc tribometer.Results showed that the optimal addition amounts of both MgP-18N and BP-18N in lithium-based grease were 3.0%.The addition of MgP-18N and BP-18N increased the extreme pressure load capacity of the lithium-based grease to 700 N and 800 N，respectively.Both MgP-18N and BP-18N demonstrated excellent high-temperature applicability.After treatment at 700 ℃，the samples maintained superior friction-reducing performance during a 10 h long-term tribological test under a 300 N load，with the friction coefficient consistently remaining at a low level (around 0.1) and with stable dynamic curves.Overall，BP-18N exhibited superior tribological performance.The morphology，elemental distribution and chemical states of the worn surfaces were analyzed using a three-dimensional (3D) optical profiler，scanning electron microscopy (SEM)，energy dispersive spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS).During the friction process，both MgP-18N and BP-18N readily adhered to the worn surfaces，forming lubricating protective films that effectively prevented direct contact between the surfaces of friction pairs.Notably，BP-18N underwent chemical reactions during friction，generating iron-boron compounds，boron oxides，and boron-nitrogen compounds，which significantly enhanced the tribological performance of lithium-based grease.